Which shows 232 − 172 being evaluated using the difference of perfect squares method?

232 − 172 = (529 + 289)(529 − 289) = 196,320
232 − 172 = 529 − 289 = 240
232 − 172 = (23 + 17)(23 − 17) = (40)(6) = 240
232 − 172 = (23 − 17)2 = (6)2 = 36

Respuesta :

difference of perfect squares is a² - b² = (a+b)(a-b)

Here, we can let 23 = a and 17 = b, so using this method, we have
23
² - 17² = (23+17)(23-17) = 40 × 6 = 240

So third option is correct.

Answer:

Your answer is 23^2 − 17^2 = (23 + 17)(23 − 17) = (40)(6) = 240, or C on your answer sheet.

Step-by-step explanation:

Lets begin!

So when a binomial is composed of two perfect squares separated by a subtraction symbol, a certain method called the difference of perfect squares can be used. The difference of perfect squares method can be done by multiplying the sum and difference of the two square roots.

So, to solve:

23^2 - 17^2 = (23 + 17)(23-17) = (40)(6) = 240

Thus being your answer.

Always here to help a Brainly citizen! (✪㉨✪) Sincerely, Kelsey from Brainly

~ #LearnWithBrainly ~